2001
DOI: 10.1016/s0735-1097(01)01127-5
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular tachycardias arising from the aortic sinus of valsalva: an under-recognized variant of left outflow tract ventricular tachycardia

Abstract: Normal heart VT with left bundle branch block, inferior axis and early precordial transition can be ablated in the majority of patients from either the left or the noncoronary aortic sinus of Valsalva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
178
0
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(189 citation statements)
references
References 16 publications
3
178
0
8
Order By: Relevance
“…9,10 In patients who cannot be ablated from the right ventricle, specific characteristics of the QRS complex during VT may point to an origin in the left ventricular outflow tract or aortic root. 5,6,11 Although, until now, no anatomically well-defined substrate for idiopathic RVOT-VT has been found, this study indicates that in some patients with a structurally normal heart and a LBBB-like VT, the site of origin is in myocardial tissue in or around the pulmonary artery. In all but 1 patient, at the site of successful ablation a sharp potential was recorded, preceding the onset of the QRS during VT by 24 to 60 ms.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…9,10 In patients who cannot be ablated from the right ventricle, specific characteristics of the QRS complex during VT may point to an origin in the left ventricular outflow tract or aortic root. 5,6,11 Although, until now, no anatomically well-defined substrate for idiopathic RVOT-VT has been found, this study indicates that in some patients with a structurally normal heart and a LBBB-like VT, the site of origin is in myocardial tissue in or around the pulmonary artery. In all but 1 patient, at the site of successful ablation a sharp potential was recorded, preceding the onset of the QRS during VT by 24 to 60 ms.…”
Section: Discussionmentioning
confidence: 61%
“…This is similar to interruption of conduction in an accessory atrioventricular pathway, either at the atrial or the ventricular end. Although specific electrocardiographic patterns during VT may indicate a left ventricular outflow tract or aortic root site of origin in some patients with idiopathic LBBB-like VT, the electrocardiographic characteristics of the VT of these 6 patients did not allow to distinguish between an RVOT and a pulmonary artery origin of the VT. 5,6,11 Although the mechanism of the VT originating from the pulmonary artery was not systematically studied, all VTs were induced during exercise testing or isoproterenol administration, indicating catecholamine sensitivity.…”
Section: Timmermans Et Al Idiopathic Pulmonary Artery Ventricular Tacmentioning
confidence: 99%
See 1 more Smart Citation
“…The first presentations of a series of patients showed a predilection for the right ventricular outflow tract (RVOT). With the development of electrophysiology it was found that a significant proportion of these arrhythmias can stem from the left ventricular outflow tract (LVOT), and in these cases the substrate is predominantly located in the supravalvular region 1 . Modern presentations of a series of patients with this entity suggest that supravalvular ventricular arrhythmias even make for 16% of the total number of patients with idiopathic ventricular arrhythmias, which suggests that this entity was not sufficiently understood in the past and it was overlooked in the majority of patients 2 .…”
Section: Anatomska I Patofizioloπka Podloga Supravalvularnim Aritmijamamentioning
confidence: 99%
“…Prvi prikazi serija pacijenata su pokazali predilekcijsku sklonost za izlazni trakt desne klijetke (RVOT). Razvojem elektrofiziologije shvatilo se da znaËajan dio tih aritmija moaee dolaziti i iz izlaznog trakta lijeve klijetke (LVOT), a u tim sluËajevima je supstrat dominantno smjeπten supravalvularno 1 . Suvremeni prikazi serija pacijenata s ovim entitetom upuÊu-ju da supravalvularne ventrikularne aritmije Ëine Ëak oko 16% od ukupnog broja pacijenata s idiopatskim ventrikularnim aritmijama, πto daje naslutiti da je ovaj entitet bio u proπlosti nedovoljno shvaÊen i u veÊine pacijenata previen 2 .…”
unclassified